PROPOSTA PARA IMPLANTAÇÃO DE BSC EM UMA INSTITUIÇÃO PÚBLICA, A PARTIR DE UM PLANEJAMENTO ESTRATÉGICO JÁ ESTRUTURADO. ESTUDO DE CASO, A DIRETORIA DE METROLOGIA CIENTÍFICA E INDUSTRIAL DO INMETRO - Barros Neto, Adauto de Oliveira (2005)
This work presents a proposal for implantation of Balanced Scorecard with the perspectives adapted for a public institution whose strategic planning is already structured. The study of the specific case of the Inmetro Scientific Metrology Directory tries to exemplify the application viability by means of the alread existent structure, starting from the analysis of their concomitant indicators with the institutional mission, vision and the strategic objectives, and the propositions of values made available to their customers and the government. It proposes a strategic map distributed in perspectives adapted to the current objectives and institutional processes, discusses the unfolding of some indicators of the structure adapted to the proposed perspectives, with the aim of suggesting actions that make possible the final BSC implantation.